Право Совета Европы : новая правовая система или подсистема международного права? - Анцупова, Татьяна Александровна; Анцупова, Тетяна Олександрівна; Ancupova, Tat'jana (My University, 2012)
In this article the term «legal system» was investigated in relation to the Council of Europe Law from the point of view of International Law. The author investigated the interpretation of the terms «legal system» and «system of law» in Theory of Law and International Law. The author identified the supranational characteristics of the Council of Europe Law, which separates the Council of Europe Law in special subsystem of the international legal system.
Анцупова Т. А. Право Совета Европы : новая правовая система или подсистема международного права? / Т. А. Анцупова // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 38-46.
Keywords: система права; правовая система; международно-правовая система; право Совета Европы; Конвенция о защите прав человека и основных свобод; Европейский суд по правам человека; правова система; міжнародно-правова система; право Ради Європи; Конвенція про захист прав людини і основоположних свобод; Європейський суд з прав людини; system of law; the legal system; the international legal system; the Council of Europe Law; Convention for the Protection of Human Rights and Fundamental Freedoms; the European Court of Human Rights